Stable isotopes in human nutrition [ laboratory methods and research applications [ - Abrams, S. A. [ (Steven A.)]; Wong, W. W. [ (William W.)] (CABI, 2003)
This book provides readers a brief glimpse into the manufacturing processes of the various stable isotopic tracers as well as a basic understanding of the principles, study designs, sample requirements, sample preparation techniques, instrumentation requirements and methods of calculation for several stable isotope methods commonly used in nutrition-related research. The book is written with the intention of generating excitement among new users and serves as a basic reference guide to experienced users. This is, therefore, appropriate for graduate-level curriculum in nutrition and for those at any level who wish to obtain an understanding of these methods.